PENGARUH CAMPURAN SISA TKKS DAN KOTORAN LARVA KUMBANG TANDUK (Oryctes rhinoceros) TERHADAP PERUBAHAN SIFAT FISIK TANAH ULTISOL DI PIRINGAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) - Rade Leferi Marpaung; Wardati Wardati; Idwar Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This purpose of this research was to determine the effect of the mixture of remaining of palm oil empty fruit bunch and the feces of hornet beetle larvae (Oryctes rhinoceros L.) physical properties changes of ultisol soil in the circle area of oil palm plant (Elaeis guineensis Jacq.). This research was conducted at PTPN V Sei Galuh Kampar Regency and at the Soil Science Laboratory, Faculty of Agriculture, Riau University. This research was conducted for third months from May 2018 to August 2018. This research was arranged on using Completely Rendomized Design (CDR) non factorial that consists of 4 treatments and 4 replications. The treatmentsof the mixture of remaining of palm oil empty fruit bunch consisted of 0 kg/plant, 5 kg/plant, 10 kg/plant, and 15 kg/plant. The data was analyzed by the analysis of variance then further test with DNMRT at the significant level of 5%. The observed parameters which is included in the physical soil properties, namely: water content, soil temperature, bulk density, particle density, total of pore space, infiltration, and organic matter. The research suggests that the application of the mixture of remaining of palm oil empty fruit bunch and the feces of hornet beetle larvae increase soil organic matter and have not improved the physical properties of the soil such as water content, soil temperature, bulk density, particle density, total of pore space, and infiltration. Keywords : soil physical properties, themixture of palm oil empty fruit bunch and the feces of hornet beetle larvae, ultisol soil